Business models for deployment and operation of femtocell networks; - Are new cooperation strategies needed for mobile operators? - Jan Markendahl; Mats Nilson (International Telecommunications Society (ITS), 2010)
In this paper we discuss different business models for deployment and operation of femtocell networks intended for provisioning of public mobile broad band access services. In these types of business cases the operators use femtocells in order to reduce investments in "more costly" macro networks since the traffic can be "offloaded" to "less costly" femtocell networks. This is in contrast to the many business cases presented in Femtoforum where femtocells mainly are discussed as a solution to improve indoor coverage for voice services in homes and small offices, usually for closed user groups The main question discussed in this paper is if "operators need to consider new forms of cooperation strategies in order to enable large scale deployment of femtocells for public access?" By looking into existing solutions for indoor wireless access services we claim that the answer is both "Yes" and "No". No, since many types of cooperation are already in place for indoor deployment. Yes, because mobile operators need to re-think the femtocell specific business models, from approaches based on singe operator networks to different forms of cooperation involving multi-operator solutions, e.g. roaming and network sharing.
Keywords: 330